Pemanfaatan SmartBook Digital berbasis Qr-Code pada Dampak Pencemaran Limbah Minyak Bumi Laut untuk Meningkatkan Keterampilan Berfikir Kritis Siswa - Andi Gafur, Irfan; Meirisa Dahlia; Putri Nur Mau Lisa (Bedelau: Journal of Education and Learning, 2023)
Instrument development was conducted to perform practicality testing on the questionnaire to determine its validity and reliability. This survey study involved 38 students. Data collection techniques were carried out by filling out the questionnaire online with the assistance of SPSS analysis program. This instrument assessed 4 constructs: product design, information content, and product effectiveness with a theoretical development model. The results of practicality testing indicated that the validity data met valid and reliable criteria